Lexical and Grammatical Transformations of Terms when Changing Communicative Situation “Doctor — Doctor” to “Doctor — Child — Parent” - V. A. Kameneva; N. V. Potapova; A. A. Rumyantseva (Научный диалог, 2023)
The issue of controversial assessment of the use of medical terminology in professional communication is considered. It is noted that the use of medical terms in communication between a doctor and an adult patient can trigger emotional tension and mistrust of the doctor’s recommendations. At the same time, it was established that patients who are familiar with medical terminology consider the use of terms by doctors to be a significant factor indicating the quality of the services provided. The question arises about the transformation of terms when changing the communicative situation “doctor — doctor” to “doctor — child — parent”. To identify and analyze transformations of medical terms, lexical-semantic and morphosyntactic analysis was used. As a result of the method of expert evaluations application, interpretations of medical terminology by doctors were obtained. It is asserted that in the communicative situation “doctor — patient and / or his representative” to remove difficulties caused by the use of highly specialized medical terms, the doctor resorts to a complex transformation of the term — explication. It is shown that explication is provided by a number of lexicalgrammatical (generalization, concretization, synonymous replacement) and syntactic techniques (adding a single prepositive definition, extended postpositive definition, adjunctive determiner, adjunctive goal), as well as stylistic means (emotionally colored vocabulary, intensifiers, conversational style).